Improving the Interaction Between Aluminum Surfaces and Polymer Coatings - Encina-Rojas, M; Paez-Collio, M; Paez-Collio, M; Muñoz-Moena, L; Muñoz-Moena, L (Elsevier B.V., 2019)
To better understand the effect of surface treatments on the efficiency of protective coatings of aluminum alloys, this study assessed different surface treatments for the aluminum alloy AA2024, including mechanical polishing, chemical etching and Ar-plasma pretreatment followed by deposition of poly(methyl methacrylate). Surface morphology, surface chemical analysis and wettability of the treated samples were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy and contact angle, respectively. Open circuit potential and electrochemical impedance spectroscopy were carried out in a 0.1 M solution of Na2SO4 as a function of exposure time. SEM images revealed that a homogeneous and well incorporated poly-(methyl methacrylate) coating was obtained by using Ar-plasma as a pretreatment. XPS spectra showed that the Al–O/Al–OH intensity ratio of the Ar-plasma pretreated samples does not show clear dependence on angle measurement, which indicates that Al(OH) and Al2O3 are not homogenously distributed on the sample surfaces. Al2O3 does not completely cover the aluminum surface, leaving some areas exposed. The measurements of the hysteresis angle showed that the Ar-plasma pretreatment favors chemical heterogeneity, which in turn increases the hydrophilicity of the coated samples, resulting in lower wettability and a greater hysteresis angle. The electrochemical results showed that the Ar-plasma pretreatment significantly improves the protective capacity of poly(methyl methacrylate). © 2018